Maternal and perinatal outcomes for women with body mass index ≥50 kg/m2 in a non‐tertiary hospital setting. (3rd October 2019) - Pratt, Anita; Howat, Paul; Hui, Lisa
Abstract : Background: Obesity is prevalent in the Australian antenatal population, but there are scarce data on the prevalence and associated outcomes of body mass index (BMI) ≥50 kg/m 2 . Aims: To examine the prevalence and outcomes for women with BMI ≥50 kg/m 2 delivering in a non‐tertiary hospital. Materials and Methods: Retrospective cohort study of women delivering a singleton pregnancy in a non‐tertiary Victorian hospital during 2011–2016. Women >180 kg were excluded as their care was managed in a tertiary centre. Maternal and perinatal outcomes were analysed by BMI group. Statistical analysis was performed using χ 2, Kruskal–Wallis and logistic regression with a significance level of 0.05. Results: Of the 18 518 births between 2011 and 2016, 99.4% had a maternal BMI recorded. The prevalence of BMI ≥50 kg/m 2 was 0.5%. Highest complication rates were observed among women with BMI ≥50 kg/m 2, including gestational diabetes (29%), hypertensive disorders of pregnancy (20%) and caesarean section (48%). Of infants born to women with BMI ≥50 kg/m 2, 12% were late‐pre‐term, 23% required special or intensive care and 20% had birth weight ≥4.0 kg. When compared with obese women with BMI 30–49 kg/m 2, women with BMI ≥50 kg/m 2 were significantly more likely to develop a hypertensive disorder of pregnancy (preeclampsia adjusted odds ratio (aOR) 3.98 (1.93–8.18), pregnancy‐induced hypertension aOR 3.55 (1.79–7.03)) and deliver a late pre‐term infant (aOR 2.45 (1.31–4.58)). Conclusions: The prevalence of severe maternal obesity in our non‐tertiary setting is higher than previous national estimates. Women with BMI ≥50 kg/m 2 are an important subgroup of the obese obstetric population who experience high rates of complications and interventions. Health services need to respond to evolving needs of the antenatal population to achieve the best outcomes for mothers and babies.